THE INFLUENCE OF THE BI RATE, INFLATION, AND EXCHANGE RATES ON THE JCI DURING THE COVID 19 PANDEMIC - Mukhtar, Saparuddin; Zahra, Siti Fatimah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the factors that affect the Composite Stock Price Index during the covid 19 pandemic. Several factors were tested such as the influence of the BI Rate, Inflation, Exchange Rate. The Composite Stock Price Index is one of the stock market indexes used by the Indonesia Stock Exchange. This index includes the price movements of all common shares and preferred shares listed on the IDX. the method used in this study is to use the multiple linear regression method). The data Iin the research is sourced from the world stock website, Bank Indonesia, the official website of the global stock exchange, and the official OJK website which is processed through the Eviews application. The results of this study indicate that The results of this study indicate that 32,43% of the JCI is influenced by the variables in this study. The BI rate has a negative effect of -5.819273 but has no significant effect on the JCI. inflation has a positive effect of 25633.30 and does not have a partial significant effect on the JCI. And the exchange rate has a significant effect partially on the JCI variable with a positive effect of 0.513